Outdoor learning model through fieldwork to ımprove physics achievement in dynamic fluid - Mundilarto; Pamulasari, Haorensa Enggar (Journal of Turkish Science Education, 2017)
This study aimed to describe the impact of the outdoor learning model on physics achievement for dynamic fluid. In this study, the outdoor learning activities were conducted through fieldwork. Fieldwork is one form of outdoor learning activities that emphasizes direct experience of students on the object being studied to link the theory to practice and improve students' skills in observation, measurement, data collection, and analysis. This study was a field trial test of physics learning model through observation to 32 students on the eleventh level physics class of senior high school in Yogyakarta Indonesia academic year of 2014/2015 as respondents. These were much divided into eight groups to do any fieldwork activities. The physics teaching and learning instructions consist of syllabus, lesson plans, worksheets, and four core competencies of assessment instruments. The instruments of data collection formed self-assessment sheet for spiritual attitudes, observation sheet for social attitudes, instrument test for physics knowledge, and observation sheet for skills. The instruments assessed the achievement of four core competencies of physics learning outcomes through fieldwork based outdoor learning. The data collected were analyzed by descriptive approach. The study states that the outdoor learning model through fieldwork which implemented can improve the core competencies of learning outcomes in dynamic fluid with the percentage of achievement of each competency is as follows: the competency of spiritual attitudes is 98%, the competency of social attitudes is 92%, the competency of physics knowledge is 78%, and the competency of skills is 92,5%.
Keywords: Outdoor learning model; fieldwork; physics achievement; dynamic fluid